Sliding Wear Study of Flame Sprayed Co-Base Powder Coatings - Kumar, Sushil; Sharma, Satpal (Journal of Coating Science and Technology, 2014)
Commercially available Co-base powder was modified with the addition of 10 wt. percentage WC which was further modified with 5 and 10 wt. percentage CrC addition in order to obtain three coatings namely Co+10 wt. percentage WC, Co+10 wt. percentage WC+5 wt. percentage CrC and Co+10 wt. percentage WC+10 wt. percentage CrC. The coatings were deposited by flame spraying process. The microstructure of these coatings mainly showed eutectic containing Co with almost same amount in three coatings. Other phases such as W dominated and Cr dominated carbides were also observed. The 10 wt. percentage CrC coating showed the highest Vickers hardness and lowest wear rate. The coefficient of friction was also observed low in the 10 wt. percentage CrC coating as compared with other coatings.